Seeking negative alphas through shorting - Mohamad, Azhar (SAGE Journals, 2017)
Shorting involves selling stocks that one does not own. Advocates of shorting argue that it is needed to make the financial market a two-way (complete) market in which investors with bearish opinions can participate. To gain from shorting, short sellers hope to buy back the shorted stocks at a lower price. Obtaining ‘negative’ alphas or abnormal returns is thus desirable for short sellers as they imply the underperformance of the stocks and that a profit has been realized. Abnormal returns, according to Fama (1998), are anomalies that tend to disappear when reasonable changes are made to the methodology used to measure them. Diamond and Verrecchia (1987), however, theorize and argue a priori that an unusually large increase in short interest will be followed by a period of negative abnormal returns. Short interest is equal to the number of shorted shares divided by the number of shares available to be shorted. Using daily short interest data for stocks traded on the London Stock Exchange for the period of September 2003 to April 2010, we employ an event study to investigate the effects that follow shorting. Alphas and abnormal returns are measured according to the Market Model (MM), the Capital Asset Pricing Model (CAPM) and the Fama–French Three-factor Model (FF3F), and are estimated using different estimation windows of 60 and 120 days. In all the methodologies under study, we find significant negative alphas following shorting.